(untitled) (World Bulletin of Public Health, 2026)
Cervical cancer remains one of the most common oncological diseases in women and poses a serious medical and social issue in many countries worldwide, including Uzbekistan. Despite advancements in screening and prevention programs, the success of early detection largely relies on the prompt assessment of individual risk factors and the application of objective diagnostic tools. The purpose of this study is to develop an integrated diagnostic and prognostic scoring scale for cervical cancer risk assessment and to create software for automating the calculation of the combined risk index. A scoring scale model based on a multifactorial approach, including clinical, behavioral, and epidemiological indicators, is proposed. Each factor is assigned a specific weight coefficient reflecting its contribution to the total risk. Using this model, an algorithm has been developed to calculate the integrated risk index, enabling stratification of patients into low, moderate, and high-risk groups.